- ANALISIS PUTUSAN NOMOR 85/PID/SUS/ 2022/PN.JAP TERHADAP PUTUSAN BEBAS TINDAK PIDANA NARKOTIKA : - - Nanda Harwijaya Arsy; Abdul Ficar Hadjar (Reformasi Hukum Trisakti, 2023)
In Decision Number 85/Pid.Sus/2022/PN.Jap, defendant Samuel Julian Yoku was acquitted by the Panel of Judges at the Jayapura Court. Despite the seizure of 61.84 grams of narcotics from the defendant, the defendant's actions actually violated Article 11 paragraph (1) in conjunction with Article 114 paragraph (1) of Law Number 35 of 2009 concerning Narcotics, as there were no users involved. This research is of a normative juridical type and descriptive in nature, utilizing secondary data and qualitative analysis to draw deductive conclusions. The research discussion results reveal that the considerations of the Panel of Judges in granting acquittal to the accused should have taken into account the consequences of the defendant's deliberate purchase of narcotics. The conclusion of this study is that the judge's considerations did not adequately uphold the principle of legality, as the defendant, based on the trial's disclosed facts, possessed cannabis-type narcotics and was supported by witness testimonies presented during the trial.